PENGARUH DURASI WAKTU METODE KANGURU TERHADAP PERUBAHAN BERAT BADAN PADA BAYI BERAT LAHIR RENDAH - Ariyani, Dwi; Sujiyatini, Sujiyatini; Theresia, Endah Marianingsih (Jurnal Kesehatan Ibu dan Anak, 2013)
According to the Demographic and Health Survey Indonesia (SDKl 2010) infant Mortality Rate (lMR) to 34 per 1,OOO Indonesian live birth rate. Amount is higher than the Millennium Development Goals (MDG's) 2015. One goal which is to reduce the infant mortality rate 25 cases per 1000 live births. One of the main causes of infant mortality are low birth weight infants 29%. Low birth weight (LBW) babies are born weighing less than 2500 g regardless of gestational age. Kangaroo method care (KMC) is an effective way to meet most of fundamental. Knowing of LBW influence kangaroo method care to changes in body weight in LBW. Quasi-experiment study with a pretest-posttest design with control group. Subject in this study were LBW is in the room Perinatology Wates and Sleman District Hospital in July-August 2013 that met the inclusion criteria. Sampling with purposive sampling. The analysis using independent t-test with confidence interval 95%. The average weight loss in the treatment group ? 4 hours kangaroo method is 34.39 grams and is <4 hours is 16.83 grams with an avenge difference of 17.566 grams. Results of statistical test p-value of 0.000 (<0.005). There is the influence duration of kangaroo method to changes in body weight on Low birth weight.